A Novel Heterozygous ACAN Variant in a Short Patient Born Small for Gestational Age with Recurrent Patellar Dislocation: A Case Report - Su Ji Kim; Jong Seo Yoon; Il Tae Hwang (Galenos Yayincilik, 2022)
ACAN variants can manifest as various clinical features, including short stature, advanced bone age (BA), and skeletal defects. Here, we report rare clinical manifestations of ACAN defects in a 9 year, 5 month-old girl born small for gestational age (SGA), who presented with short stature, and was initially diagnosed with idiopathic growth hormone deficiency. She displayed several dysmorphic features, including genu valgum, cubitus valgus, and recurrent patellar dislocations. She presented with progressive advancement of BA compared with chronological age. Whole exome sequencing confirmed the presence of a novel heterozygous nonsense variant, c.1968C>G, p.(Tyr656*), in ACAN. ACAN variants should be considered in short stature patients born SGA with joint problems, particularly those with recurrent patellar dislocation and genu valgum.